PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VIII SMP NEGERI 10 PADANG - Yasri, Muradhatul Aina; Harisman, Yulyanti (Jurnal Edukasi dan Penelitian Matematika, 2024)
Student math proficiency demands problem-solving skills. The 2023/2024 grade VIII problem-solving skills of SMP Negeri 10 Padang pupils are still below average. Insufficient learning model prevents skill acquisition. We recommend using Problem-Based Learning (PBL) to solve challenges. A Nonequivalent Posttest-Only Control Group Design pseudo-experiment was used. Using basic random sampling, class VIII.1 was the experimental group and VIII.3 was the control group. T-test results for hypothesis testing showed a P-value of 0.000, which is less than 0.05. H0 is rejected. So, class VIII.1 students who utilized the PBL approach solved mathematical problems better than class VIII.3 students who used the conventional way.Keywords – PBL, Mathematical Problem Solving Ability, Conventional Learning